Fostering financially savvy generations: the intersection of financial education, digital financial misconception and parental wellbeing - Senduk, Feibry Feronika Wiwenly; Djatmika, Ery Tri; Wahyono, Hari; Churiyah, Madziatul; Mahasneh, Omar; Arjanto, Paul (Frontiers in Education, 2024)
Amid rapid technological advancements and the proliferation of digital financial services, this research underscores the critical importance of financial literacy as a foundational element for making informed financial decisions and managing the complexities associated with modern financial environments. This study examines the impact of personal financial education on financial management behavior, digital financial misconceptions, and parental well-being among high school students in Indonesia using Structural Equation Modeling (SEM). The findings reveal that effective financial education not only enhances students' financial management capabilities but also plays a significant role in reducing digital financial misconceptions and improving parental well-being. By implementing robust financial education programs in schools, this study demonstrates the potential for significantly improving financial behaviors and decision-making among youth. Furthermore, the research highlights the necessity of integrating financial education into the curriculum to equip future generations with the skills required to navigate increasingly complex financial markets successfully. The results advocate for policy interventions that prioritize financial literacy education to foster economic stability and well-being at both individual and societal levels.